O efeito mais que etnográfico: Literatura como retomada, autoria e ativismo de mulheres indígenas - Barbosa, Thais Viana (2024)
This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001 and it consists of an ethnography of the complete works of two Brazilian indigenous female writers, whose publications have strengthened the historical struggle of indigenous peoples in Brazil. Seeking to demonstrate that contemporary indigenous literature is an extension of indigenous cosmopolitics, the aesthetic, political, and politicizing character of each publication is discussed. By bringing together concepts central to anthropology and literary studies, it is evident that the writing of Eliane Potiguara and Márcia Wayna Kambeba-Omágua traverses bodies and territories in a movement that updates and reaffirms indigenous onto-epistemic diversity in Brazil and Latin America. By bringing indigenous and non-indigenous worlds into relation, this literature acknowledges conflict and alterity as something that manifests between partially connected worlds. In their testimonial, autobiographical, and auto ethnographical aspects, Potiguara and Kambeba's publications delineate indigenous cosmologies onto literature and develop decolonizing epistemologies. As part of indigenous activism, this literature has demonstrated itself as a reclaiming, activism, and authorship in a writing that reverberates worlds and their human and non-human constituents.